Localization in iOS apps : enable support for multiple languages in your apps - Aggarwal, Aman (Apress, 2018)
"Learn how to make iOS apps that target multiple languages with user interfaces that can handle varying directions of text and other linguistic conventions. Support for other languages, not just simple translation but full support for conventions, is a key part of successful apps as most people around the globe will want to interact with your app in their native language. With this course, you'll learn to match your app to the device language of your user as well as providing the ability to change the language to something other than that provided by the device as a default. You'll also learn how to incorporate images and other elements that interact correctly with the conventions of different languages. After this course, your apps will be compliant with many of the world's prominent languages and the audience for your applications will grow!"--Resource description page